Screening and evaluation of active compounds in polyphenol mixtures by HPLC coupled with chemical methodology and its application. (15th July 2017) - Zhao, Yue; Wang, Ying; Jiang, Zi-Tao; Li, Rong
Highlights: An off-line HPLC method was developed for rapid screening of polyphenols. Method with wonderful linearity and precision was easy to implement. Method was applied to rapid screening polyphenols from complex natural extract. Activities of antioxidant components in C. endivia extract were first evaluated. Abstract: An off-line high performance liquid chromatography (HPLC) coupled with chemical methods has been developed to evaluate antioxidant activity of 11 standard polyphenol compounds (SPCs) and vitamin C (Vc) in terms of radical scavenging abilities. The structure–activity relationships of each SPC were also discussed. SPCs showed different abilities in scavenging 2, 2-diphenyl-1-picrylhydrazyl (DPPH ), 2, 2′-azinobis-3-ethyl-benzthiazoline-6-sulphonate (ABTS + ) and hydroxyl ( OH) free radicals. Among SPCs, quercetin and kaempferol, as typical flavonoids, displayed the greatest radical-scavenging activities and even exhibited higher activity in OH radical removal ability than that of Vc. Furthermore, the proposed method was also applied to screening polyphenolic antioxidant components from Cichorium endivia L. ( C. endivia ) seed extract. The results indicated that cynarin in the extract was a more active compound to scavenge DPPH and ABTS + radicals than chlorogenic acid, while chlorogenic acid had stronger capacity in scavenging OH free radicals.